Basophilic peripheral nerve inclusions in a patient with L144F SOD1 amyotrophic lateral sclerosis - Aleksić, Dejan; Perić, Stojan; Milenković, Sanja; Janković, Milena; Rakočević-Stojanović, Vidosava; Stević, Zorica (Vojnosanitetski pregled, 2023)
Introduction. Histopathological findings of various inclusions were reported in the central nervous system of amyotrophic lateral sclerosis (ALS) patients but not in the peripheral nerves. Case report. We present a 66-year-old man with lower limb weakness, with later development of weakness in the upper limbs and loss of sphincter control. Neurological examination showed the affection of both upper and lower motor neurons. He had paresthesia on the left side of his body and socks-distribution numbness. Histopathology of the sural nerve and genetic report showed basophilic periodic acid-Schiff (PAS)-positive intra-axonal inclusions and heterozygous L144F mutation in the exon 5 of the SOD1 gene. Conclusion. It seems that the presence of the basophilic peripheral nerve inclusions may suggest a diagnosis of SOD1-positive ALS.
Keywords: amyotrophic lateral sclerosis; diagnosis; genes; histological techniques; mutation; staining and labeling; superoxide dismutase